2020
DOI: 10.5194/acp-20-4059-2020
|View full text |Cite
|
Sign up to set email alerts
|

Open cells exhibit weaker entrainment of free-tropospheric biomass burning aerosol into the south-east Atlantic boundary layer

Abstract: Abstract. This work presents synergistic satellite, airborne and surface-based observations of a pocket of open cells (POC) in the remote south-east Atlantic. The observations were obtained over and upwind of Ascension Island during the CLouds and Aerosol Radiative Impacts and Forcing (CLARIFY) and the Layered Smoke Interacting with Clouds (LASIC) field experiments. A novel aspect of this case study is that an extensive free-tropospheric biomass burning aerosol plume that had been transported from the African … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 56 publications
6
37
1
Order By: Relevance
“…The CER retrieved from the 1.6 µm channel is lower than the one retrieved from the 2.1 µm by 0.5 µm, which is consistent with the analysis from Platnick (2000). Differences in the cloud parameterization, such as the refractive index and the effective variance, also affect the CER retrieval (Arduini et al, 2005;Painemal and Zuidema, 2011;Platnick et al, 2019), although the impact is expected to depend on the observed scattering angle. Biases could also arise from an offset in the absolute calibration of the SEVIRI 1.64 µm band compared to MODIS (Meirink et al, 2013).…”
Section: Statistical Comparisonssupporting
confidence: 74%
“…The CER retrieved from the 1.6 µm channel is lower than the one retrieved from the 2.1 µm by 0.5 µm, which is consistent with the analysis from Platnick (2000). Differences in the cloud parameterization, such as the refractive index and the effective variance, also affect the CER retrieval (Arduini et al, 2005;Painemal and Zuidema, 2011;Platnick et al, 2019), although the impact is expected to depend on the observed scattering angle. Biases could also arise from an offset in the absolute calibration of the SEVIRI 1.64 µm band compared to MODIS (Meirink et al, 2013).…”
Section: Statistical Comparisonssupporting
confidence: 74%
“…Higher effective radius and rain rates were observed inside this POC during the CLouds-Aerosol-Radiation Interactions and Forcing flight campaign (20 to 40 µm) compared with the surrounding cloud deck (10 to 20 µm) as described in Abel et al (20). Similar behavior was observed in open cellular broken cloud conditions during the Variability of the American Monsoon Systems Ocean-Cloud-Atmosphere-Land Study campaign (21) and from a climatology of POCs in satellite observations (20). We conclude that there is confidence in the ability of the satellite data to capture microphysical responses along the trajectories used in this study.…”
Section: Lagrangian Trajectory Frameworksupporting
confidence: 62%
“…Satellite retrievals are generally more uncertain in broken cloudy conditions due to the general inability to account for complex three-dimensional (3D) radiative transfer and absorption (19). Higher effective radius and rain rates were observed inside this POC during the CLouds-Aerosol-Radiation Interactions and Forcing flight campaign (20 to 40 µm) compared with the surrounding cloud deck (10 to 20 µm) as described in Abel et al (20). Similar behavior was observed in open cellular broken cloud conditions during the Variability of the American Monsoon Systems Ocean-Cloud-Atmosphere-Land Study campaign (21) and from a climatology of POCs in satellite observations (20).…”
Section: Lagrangian Trajectory Frameworkmentioning
confidence: 63%
“…BBAs over the Southeast Atlantic have 500 nm singlescattering albedo ranging between 0.83 and 0.89 (Pistone et al, 2019), which indicates a significant absorbing component to the BBA layer. The warming associated with shortwave absorption by BBAs over the Southeast Atlantic can be amplified by the evaporation of cloud droplets, the semidirect effect (Hansen et al, 1997;Ackerman et al, 2000). Aerosols above a reflective cloud layer absorb more solar radiation than aerosols below or within cloud, which affects cloud formation (Haywood and Shine, 1997) and the region's aerosol direct radiative effect (Keil and Haywood, 2003;Cochrane et al, 2019).…”
Section: Introductionmentioning
confidence: 99%